Analisis Kebebasan Pers dalam Novel Laut Bercerita Karya Leila S. Chudori - Niken Ayu Cahyani; Ahmad Harun Yahya; Muslimin . (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This research is based on the fact that journalists' editorial statements in novels are often used by the press (or journalists/writers with press backgrounds) to describe the state of the press world for several important reasons, namely greater freedom of expression. Leila S. Chudori's novel Laut Bercerita tells the dramatic story of student activists during the New Order era in Indonesia. The purpose of this research is to examine press freedom in Leila S. Chudori's novel Laut Bercerita. The title of the paper is "Analysis of Press Freedom in Leila S. Chudori's Novel Laut Bercerita." This research uses Critical Journalism Theory, an approach derived from the tradition of critical theory and agenda-setting theory developed within the Frankfurt School. This research uses a qualitative analysis method (liberal research), analyzing Leila S. Chudori's novel Laut Bercerita. The results of the research on press freedom in Leila S. Chudori's novel Laut Bercerita indicate that the lack of press freedom in journalism is closely related to repressive practices of power. The silencing of the press has implications for human rights violations, the spread of propaganda, and the loss of state oversight. This novel simultaneously critiques the authoritarian press system and emphasizes the importance of press freedom in a democratic life..